“May-Thurner syndrome as an underlying cause of unilateral left-sided deep vein thrombosis in a young healthy female: A case report” - Khaled Sawafta; Fadi Yousef; Hani Abu Hijleh; Wasef Abdat; Yousef Samara; Tasbeeh Al-Kharraz (Radiology Case Reports, 2025)
May-Thurner syndrome (MTS), iliac vein compression syndrome, also called Cockett syndrome, is a vascular disease caused by the compression of the left common iliac vein (LCIV) by the right common iliac artery (RCIA) against the lumbar vertebrae. This anatomical defect can lead to venous stasis especially in the left lower limb, and this increases the risk of deep venous thrombosis (DVT). Because routine screening is not standard practice, MTS frequently remains asymptomatic, and its prevalence is probably underestimated. Our case report presents 33 year old women with no thrombotic condition history who complained from a left leg swelling, pain, and stiffness over 5 days. Computed tomography angiography (CTA) confirmed a diagnosis of MTS, and Doppler ultrasonography confirmed extensive DVT in the left lower limb. After receiving conservative treatment with enoxaparin, the patient switched to apixaban therapy. The significance of identifying MTS as a possible cause of unilateral left-sided DVT is highlighted by this case, especially in young, otherwise healthy women. Recurrent DVT and chronic venous insufficiency are among the complications that can be prevented by early detection with imaging and anticoagulation treatment. Patients with atypical DVT presentations may benefit from earlier diagnosis and treatment made possible by greater knowledge of MTS.